Modeling Techniques in The Perspective of Islamic Guidance and Counseling - Ramazana Ramazana; Nurjannah Nurjannah (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2023)
This research is a literature study that discusses Modeling Techniques which is a part of the Social learning theory developed by Albert Bandura. Modeling is the process of counselees learning from observing other people with the aim of solving the psychological problems they face. Modeling technique is a form of therapy that has not been widely used today. This study aims to develop Modeling Techniques in the perspective of Islamic Guidance and Counseling. Based on the studies carried out for this purpose, it can find similarities and differences in modeling in Islam through the existence of a series of similarities that are found with different mentions. In Islamic studies, modeling is known as Uswatun Hasanah (Series of Modeling) and stories that describe the life of the former Ummah which contain substantial good and bad will have different and varied consequences so that they become a model of life that should be exemplified. Islamic modeling is in the form of stories and examples of life that aim to achieve happiness (Maslahah) in the afterlife.